Crystal lattice tilt analysis in gradient composition layers by electron and X-ray diffraction. (December 2019) - Snigirev, L A; Kirilenko, D A; Pirogov, E.V.; Baidakova, M V; Bert, N A
Abstract: The combination of X-ray tilt-azimuth figure, reciprocal space map and transmission electron microscopy in selected area electron diffraction mode was applied to analyse the tilt of the MBE-grown 1.2-μm thick convex-graded Inx Al1-x As (x=0.05-0.80) metamorphic buffer layer on singular GaAs (001) substrate. The combination of the techniques is demonstrated to enable the determination of the tilt angle as well as the tilt direction together with monitoring of the tilt development along the growth direction. For the studied metamorphic buffer layer as an example, the tilt direction was deduced to be 20° off the (110) GaAs substrate crystallographic plane. The tilt angle of (002) buffer layer planes was observed to rapidly rise to 0.6° near the layer-substrate interface and then to slowly increase to 1.4° with the approach toward the surface.